Description of Attachment Patterns of Institutionalized Minors with Behavior Problems - Méndez Tapia, Lorena; González Bravo, Luis (Revista de Psicología, 2002)
The present investigation asesses attachment patterns in institutionalized children with conduct problems. In contrast, to previous designs which followed the Ainsworth Strange Situation or the AAI procedures, this investigation uses DSM IV criteria and the Randolph Attachment Disorder Questionaire . After obtaining significant RADQ validity and confiability scores, it was found that 37,9% of the children with behaviour problems met the DSM IV criteria for Reactive Attachment Disorder and 20,7% met the diagnostic criteria for AD. Furthermore, the most frecuent attachment pattern was the Anxious type, (38,3 %). Finally, a review of the impact and limitations of the results is presented.